1990
DOI: 10.1111/j.1558-5646.1990.tb03804.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF A HAEMATOPHAGOUS MITE ON THE BARN SWALLOW (HIRUNDO RUSTICA): A TEST OF THE HAMILTON AND ZUK HYPOTHESIS

Abstract: Abstract.-I tested three assumptions of the Hamilton and Zuk hypothesis (1982), which suggests that the extravagant male plumage of many bird species allows females to choose mates that are resistant to the parasites exploiting the host population at a given time. By choosing such males as mates, females will rear offspring carrying the genes for resistance. I tested three necessary conditions for the Hamilton and Zuk model: (1) whether parasites affect the fitness of their hosts; (2) whether there is heritabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…Many observational and experimental studies support Hamilton & Zuk's hypothesis by revealing a negative relationship between a male's parasite load and the showiness of his sexual characters (e.g. MÖller 1988MÖller , 1990Clayton 1990;Milinski & Bakker 1990;Zuk et al 1990a,b;Houde & Torio 1992;Saino & MÖller 1996; for reviews, see Clayton (1991) and MÖller & Saino (1994)). These same studies also provide evidence for a discriminatory preference of females for the showiest and least infected males.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many observational and experimental studies support Hamilton & Zuk's hypothesis by revealing a negative relationship between a male's parasite load and the showiness of his sexual characters (e.g. MÖller 1988MÖller , 1990Clayton 1990;Milinski & Bakker 1990;Zuk et al 1990a,b;Houde & Torio 1992;Saino & MÖller 1996; for reviews, see Clayton (1991) and MÖller & Saino (1994)). These same studies also provide evidence for a discriminatory preference of females for the showiest and least infected males.…”
Section: Introductionmentioning
confidence: 93%
“…heritable. Genetically based variations in immune response are well-recorded in experimentally controlled studies (Wassom et al 1974(Wassom et al , 1986Wakelin 1975;Wakelin & Blackwell 1988;MÖller 1990;Wakelin & Rose 1990;Wakelin & Apanius 1997). Most recorded examples are of continuous variation between extremes of resistance and susceptibility to parasites, although some examples are of discontinuous variation, where a host falls into one or another category.…”
Section: Introductionmentioning
confidence: 99%
“…Long-tailed males enjoy several kinds of mating advantages, as demonstrated by observations and experiments (Møller, 1988(Møller, , 1994Saino et al, 1997). This secondary sexual character is condition-dependent because poor conditions in the winter quarters, ectoparasites and radioactive contamination cause the production of smaller characters (Møller, 1990(Møller, , 1992(Møller, , 1993. Long tails of males may improve manoeuvring ability (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a correlational study, Boulinier et al (1997) found a positive relationship for tick load between parents and o¡spring. Strong support comes from MÖller (1990), who demonstrated in a cross-fostering experiment that mite populations on nestling barn swallows (Hirundo rustica) were partly determined by sibling relationships. Signi¢cant additive genetic variation in cell-mediated immunity was shown in nestling barn swallows by Saino et al (1997a).…”
Section: Introductionmentioning
confidence: 99%